Multipath effects of berberine on peach Brown rot fungus Monilinia fructicola. (February 2019) - Pei, Qinghui; Li, Ying; Ge, Xizhen; Tian, Pingfang
Abstract: The brown rot disease caused by fungus Monilinia fructicola severely reduces the yield of peach and other stone fruits. Earlier, we found that berberine (BBR), one of isoquinoline alkaloids, strongly halts the growth of M . fructicola . However, the underlying mechanisms remain unclear. Here we report that BBR inhibits M. fructicola at multiple levels. Scanning electronic microscope (SEM) analysis of BBR-treated M . fructicola revealed morphological abnormality of spores and hyphae. Enzyme activity assay showed BBR's significant inhibition on the activities of enzymes succinate dehydrogenase (SDH), malate dehydrogenase (MDH) and ATPase in mitochondrion, indicating that BBR impedes mitochondrial functions. Furthermore, transcriptomic analysis of BBR-induced M . fructicola revealed that most differentially expressed genes were involved in MAP kinase activity, activation of MAPKK activity, and ADP binding. Overall, these results indicate that BBR inhibits M. fructicola through multipath mechanisms, including destruction on cells, interference of mitochondrial functions, and repression of DNA replication and gene expression. Highlights: The results in this study indicate that BBR inhibits M. fructicola through multiple mechanisms. This is the first transcriptomic analysis of M. fructicola exposed to berberine. We propose a model of M. fructicola response to berberine.